Technostress and Organizational Culture in the Software Industry - López Galicia, Giselle Araceli; Gómez Ortiz, Rosa Amalia (Mercados y Negocios, 2023)
This paper critically reviews the literature on technostress, the organizational culture of employee well-being, and the relationship between the concepts in the software industry workers. For this task, it is crucial to describe the characteristics of the software industry. After that, the definition and dimensions of technostress and organizational culture are explained. Finally, the relationship between technostress and organizational culture is presented.